2015
DOI: 10.4088/jcp.13m08863
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Functional and Clinical Outcome in Early-Onset First-Episode Psychosis

Abstract: Baseline clinical assessments have a better predictive value than biological assessments for 2-year follow-up functioning of children and adolescents with a first episode of psychosis. Patients with primary negative symptoms at baseline continue to have negative symptoms 2 years later, and neurostructural markers predict these. Clinicians must still rely on clinical variables to judge the functional prognosis of early-onset first psychotic episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…These results underscore the multifaceted aetiology of these conditions and demonstrate the degree of overlap between the subgroups. In this study, SZ patients often occupied an intermediate level between DP and MP patients, and previous research has already proposed SA disorder as the intermediate between SZ and MP (Benabarre et al, 2001;Parellada et al, 2015;Tamminga et al, 2013;Tondo et al, 2016). These findings contribute to the ongoing discussion concerning the existence of a psychosis spectrum (Crow, 1990;Van Os et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results underscore the multifaceted aetiology of these conditions and demonstrate the degree of overlap between the subgroups. In this study, SZ patients often occupied an intermediate level between DP and MP patients, and previous research has already proposed SA disorder as the intermediate between SZ and MP (Benabarre et al, 2001;Parellada et al, 2015;Tamminga et al, 2013;Tondo et al, 2016). These findings contribute to the ongoing discussion concerning the existence of a psychosis spectrum (Crow, 1990;Van Os et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…Most research to date on the association of psychosocial risk factors with psychosis has focused on SZ psychoses (Ayesa-Arriola et al, 2016;Compton, Kelley, & Ionescu, 2014;Crow, 1990;Jablensky, 2006). There have, in addition, been several studies comparing psychosocial factors in SZ, manic psychoses (MP) and schizoaffective (SA) psychoses in FEP; the results of these studies identify SA psychosis as an intermediate phenotype between SZ and bipolar disorder (BD), including on psychosocial variables such as age, education and marital status (Benabarre et al, 2001;Cannon, Jones, Gilvarry et al, 1997;Cheniaux, Landeira-Fernandez, Telles et al, 2008;Conus, Cotton, Schimmelmann, McGorry, & Lambert, 2007;Murray et al, 2004;Parellada, Castro-Fornieles, Gonzalez-Pinto et al, 2015;Strauss, Vertinski, Vogel, Ringdahl, & Allen, 2016;Tamminga, Ivleva, Keshavan et al, 2013;Tondo, Vázquez, Baethge et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…13,19 Recent studies on dimensional models during the course of the disease have suggested that disorganization may represent an independent dimension (which some authors term the cognitive dimension), 19 which alongside the psychotic dimension (e.g., hallucinations and delusions) and the other two or three dimensions (depressive dimension; negative symptoms dimension; hostility or excitement dimension), make up the symptomatic constellation for the diagnosis of schizophrenia, BD, and other psychotic syndromes. 18,19,31 The similar occurrence of psychotic symptoms during first manic episode in both age groups (early and late adolescents) of our sample may suggest that disorganization or psychotic manifestations were not an age-dependent phenomenon, but rather were related to the severity of the disorder, i.e., a BDspecific phenomenon as suggested by Angst. 11 Most of our patients presented simultaneous manifestations of manic, psychotic, and disorganized symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…We recommend that clinicians consider BD as an alternative diagnosis parallel to schizophrenia when dealing with children and adolescents in first psychotic episode. 7,14,18 Researchers have called for improved training of practitioners to recognize pathological delusions and hallucinations, as well as different dimensions of a psychotic syndrome in children and adolescents. 7,13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation